1982
DOI: 10.1161/01.str.13.1.59
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high dose mannitol on cerebral blood flow in dogs with normal intracranial pressure.

Abstract: SUMMARY In normal dogs, bolus administration of a very high dose of mannitol (2 gm/kg) resulted in a small, transient increase in cerebral blood flow (CBF) of approximately 8 percent lasting less than 10 minutes followed by a significant reduction in CBF of approximately 20 percent lasting at least three hours. The increase in CBF may in part be related to changes in cardiovascular and hematological parameters. No explanation is available for the reduction below control values but, since urine losses were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…22 All of these factors would increase rCBF, and increases have been measured in humans with glioma," in normal baboons, 20 and in dogs. 21 However, in animals this flow increase has been transient, and a more persistent decrease in CBF has been noted after 20 minutes." 21 Mechanisms for this decrease have not been postulated.…”
Section: Resultsmentioning
confidence: 99%
“…22 All of these factors would increase rCBF, and increases have been measured in humans with glioma," in normal baboons, 20 and in dogs. 21 However, in animals this flow increase has been transient, and a more persistent decrease in CBF has been noted after 20 minutes." 21 Mechanisms for this decrease have not been postulated.…”
Section: Resultsmentioning
confidence: 99%
“…In healthy volunteers, intravenous infusion of hypertonic dextrose or NaCl solutions has been found to increase forearm blood flow as a result of a decrease in resistance [35] . Similarly, intravascular infusion of hypertonic solutions has been shown to increase cerebral blood flow [36,37] . Sasaki and co-workers suggested that hypertonic solutions produce non-specific vasodilation of cerebral arteries by inhibiting the influx of external Ca 2+ rather than the release of intracellularly stored Ca 2+ [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The first effect of mannitol is rheological. An immediate expansion of intravascular volume lowers the hematocrit and blood viscosity while increasing cerebral blood flow and cerebral oxygenation which lead to vasoconstriction and decrease in ICP 5,12,17) . The second effect is an osmotic effect to shift brain tissue water into the intravascular space and reduce cerebral extracellular free water by the establishment of an osmotic gradient along the blood-brain barrier 6,7) .…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic therapy with mannitol is effective in reducing ICP by its rheological and osmotic effects 5,7,12,17) . Theoretically, its osmotic effect is produced in the brain with an intact blood-brain barrier (BBB) and extravasation of mannitol through a disrupted BBB may exacerbate vasogenic brain edema.…”
Section: Introductionmentioning
confidence: 99%